Struvite recovery from anaerobically digested liquor of food waste by using precipitation technique - Fatin Sualin (2018)
The growing number of human population throughout the world is proportional to the amount of wastes produced. Previous research showed that food waste has been the main components and the highest waste contributor of municipal solid waste. The common disposal technique of food waste is by landfilling and incineration. However, these techniques lead to environmental problems including the greenhouse gas (GHG) effect and odour problem. The effort of separating recyclable waste which include glass, plastics and paper was great, however it is best to also gain benefits from food waste thus decreasing the amount of waste being landfilled. In this study, food waste was chosen as a substrate of anaerobic digestion in recovering struvite which is a mineral rich in phosphorus. Different composition of food waste ( carbohydrate rich- food waste, fibre rich- food waste and protein rich- food waste) undergone series of analysis and treatment including determination of ions concentration and anaerobic digestion before the final of recovering process. Before anaerobic digestion was performed some physical and chemical properties of all composition of food waste were conducted. Anaerobic digestion of food waste was performed at controlled temperature (37°C) and pH (6.8-7.2) for 15 days. The total and volatile solids were then again determined as well as the reduction after anaerobic digestion. The struvite precipitation using the digested liquor was carried out at room temperature for 1 hour. The total and volatile solids contents and also its reduction after anaerobic digestion were found the highest in carbohydrate-rich food waste with value of 51.26% and 97 .48% for the content, and 46.69% and 89.19% for the reduction, respectively. The results show that protein-rich food waste attained the highest phosphorus recovery after anaerobic digestion process with concentration of 500.86 mg/L. Fifty one percent of calcium content in protein-rich food waste was successfully removed using EDTA chelation treatment. The anaerobically digested liquor of protein-rich food waste was then used to undergo precipitation process using molar ratio 1: 1: 1 of Mg: NH4: PQ4: NH4. About 58% of struvite was successfully recovered from the proteinrich food waste and it was calculated that every lg of wet food waste can produce 170 mg struvite. The struvite precipitate was then applied to lettuce and tomatoes plants to investigate its effect towards plant growth. The results show that struvite was able to enhance the plants growth by increasing the weight yield (lettuce), length (tomatoes) and also leaves counts (tomatoes) of the plants. Overall, this study indicates that food waste can be a suitable substrate for anaerobic digestion for phosphorus recovery in the form of struvite, a slow-release fertilizer, thus, promotes waste to wealth concept.